Religion as a Source of Islamic Ethics and its Impact on the Islamic Accounting System - Czerny, Małgorzata M.E. (Acta Universitatis Lodziensis. Folia Oeconomica, 2021)
The article introduces religion as a source of Muslim ethics and shows how it is shaping the system of Islamic accounting and the ethical behaviour of Muslim accountants. Cultural differences are an increasingly important factor to be taken into account in running a business. They are also the subject of scientific research, for example, in the context of their impact on the development of accounting systems in various cultural circles. The relevant reference literature and the Qur’an were used for qualitative analysis carried out by means of induction and deduction methods. The analysis conducted indicates that although the scope of ethical codes in Muslim and non‑Muslim countries is very similar, in the case of Islam, its message is strengthened by religion seen as a source of law as well as professional ethics. This means that the legal sanctions envisaged for breaking the rules are accompanied by the fear of being excluded from the community and losing an opportunity for salvation. This article can fulfill an informative role, allowing the reader to understand the reasons for some differences in perceiving ethical issues and the way of doing business in different cultural circles.